Seismic Hazard Identification On North Banda Arc Region Using Gutenberg-Richter Law - Lestari, Silvia; Sungkono, Sungkono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
North Banda Arc region has high risk of significant earthquake due its complex tectonic configuration. in order to assess seismic hazard potential on north Banda Arc region, Gutenberg-Richter (G-R) Law is applied using Earthquake catalogue from 1970 to 2023. The results are G-R parameters including Mc, a, and b, where the the spatial parameters (a and b values) and temporal parameter (b-value) are applied to investigate the seismic hazard in the north Banda Arc Region. The spatial results show that two regions with high risk to release stress in strong earthquake are on eastern Seram Island and between eastern Buru and western Seram Island including its smaller island nearby. On the other side, temporal earthquake shows decreasing b-value indicates increasing effective stress that could lead to strong earthquake.